Fine particulate matter (PM(2.5)) in China at a city level - Zhang, Yan-Lin (Sci Rep, 2015)
This study presents one of the first long term datasets including a statistical summary of PM(2.5) concentrations obtained from one-year monitoring in 190 cities in China. We found only 25 out of 190 cities could meet the National Ambient Air Quality Standards of China, and the population-weighted mean of PM(2.5) in Chinese cities are 61 μg/m(3), ~3 times as high as global population-weighted mean, highlighting a high health risk. PM(2.5) concentrations are generally higher in north than in south regions due to relative large PM emissions and unfavorable meteorological conditions for pollution dispersion. A remarkable seasonal variability of PM(2.5) is observed with the highest during the winter and the lowest during the summer. Due to the enhanced contributions from dust particles and open biomass burning, high PM(2.5) abundances are also found in the spring (in Northwest and West Central China) and autumn (in East China), respectively. In addition, we found the lowest and highest PM(2.5) often occurs in the afternoon and evening hours, respectively, associated with daily variation of the boundary layer depth and anthropogenic emissions. The diurnal distribution of the PM(2.5)-to-CO ratio consistently displays a pronounced peak during the afternoon periods, reflecting a significant contribution of secondary PM formation.